Comparative Risk of Nonvertebral Fractures Among Patients With Rheumatoid Arthritis Treated With Biologic or Targeted Synthetic Disease‐Modifying Antirheumatic Drugs. Issue 8 (1st July 2021) - Pawar, Ajinkya; Desai, Rishi J.; He, Mengdong; Bessette, Lily; Kim, Seoyoung C.
Abstract : Objective: The objective of this study was to compare the incidence rate of nonvertebral osteoporotic fractures (NVFs) in patients with rheumatoid arthritis (RA) initiating one of the nine biologic or targeted synthetic disease‐modifying antirheumatic drugs (b/tsDMARDs). Methods: We analyzed claims data from Optum (2008 to March 2019), Medicare, and MarketScan (2008‐2017) to identify adults with RA who newly initiated b/tsDMARDs. Adalimumab was the most frequently used and was thus selected as a reference. The primary outcome was a composite of incident NVFs, including hip, humerus, pelvis, and wrist fractures, based on validated algorithms. We adjusted for greater than 70 potential confounders in each database through propensity score–based inverse probability treatment weighting. Follow‐up time started the day after cohort entry until the first occurrence of one of the following: outcome, treatment discontinuation, switching, nursing home admission, death, disenrollment, or end of study period. For each drug comparison, weighted Cox proportional hazards models estimated the hazard ratios (HRs) and 95% confidence intervals (CIs). Secondary analyses were conducted in patients switching from a tumor necrosis factor inhibitor to a different b/tsDMARD. Results: A total of 134, 693 b/tsDMARD initiators were identified across three databases. The adjusted HRs showed similar risk of composite NVFs in all b/tsDMARD exposures compared with adalimumab: abatacept, HR 1.03 (95% CI 0.82‐1.30); certolizumab, HR 1.08 (95% CI 0.79‐1.49); etanercept, HR 1.12 (95% CI 0.89‐1.40); golimumab, HR 0.91 (95% CI 0.59‐1.39); infliximab, HR 1.03 (95% CI 0.84‐1.28); rituximab, HR 1.07 (95% CI 0.74‐1.55); tocilizumab, HR 1.24 (95% CI 0.71‐2.17); and tofacitinib, HR 1.07 (95% CI 0.69‐1.64). Secondary analyses showed similar results. Conclusion: This multidatabase cohort study found no differences in the risk of NVFs across individual b/tsDMARDs for RA, which provides reassurance to physicians prescribing b/tsDMARDs, especially to patients at high risk of developing NVFs.